2023
DOI: 10.1371/journal.pone.0271572
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of magnetic resonance elastography and point-shear wave elastography for significant hepatic fibrosis screening: Systematic review and meta-analysis

Abstract: The hepatic diseases are extremely common in clinical practice. The correct classification of liver fibrosis is extremely important, as it influences therapy and predicts disease outcomes. The purpose of this study is to compare the diagnostic performance of point-shear wave elastography (pSWE) and magnetic resonance elastography (MRE) in the hepatic fibrosis diagnostic. A meta-analysis was carried out based on articles published until October 2020. The articles are available at following databases: MEDLINE, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Also, the same meta-analysis showed a diagnostic accuracy in detecting liver cirrhosis with an sAUC, sensitivity, and specificity of 0.90, 81%, and 90%, respectively. A meta-analysis by Schambek J.P.L et al [44] analysed the diagnostic performance of MRE and point shear wave elastography (pSWE) with an excellent diagnostic accuracy of MRE in staging METAVIR F2 patients with a pooled sensitivity and specificity of 0.94 and 0.95 in MRE, higher than the pooled sensitivity and specificity of pSWE. In this meta-analysis, MRE proved to be an important tool for the early diagnosis of liver fibrosis, reducing the role of biopsies in F2 fibrosis patients.…”
Section: Accuracy Of Mrementioning
confidence: 99%
“…Also, the same meta-analysis showed a diagnostic accuracy in detecting liver cirrhosis with an sAUC, sensitivity, and specificity of 0.90, 81%, and 90%, respectively. A meta-analysis by Schambek J.P.L et al [44] analysed the diagnostic performance of MRE and point shear wave elastography (pSWE) with an excellent diagnostic accuracy of MRE in staging METAVIR F2 patients with a pooled sensitivity and specificity of 0.94 and 0.95 in MRE, higher than the pooled sensitivity and specificity of pSWE. In this meta-analysis, MRE proved to be an important tool for the early diagnosis of liver fibrosis, reducing the role of biopsies in F2 fibrosis patients.…”
Section: Accuracy Of Mrementioning
confidence: 99%
“…Unlike 1D-TE, pSWE utilizes B-mode ultrasound to directly visualize and select the region of interest, whereas 1D-TE is heavily dependent on A-mode ultrasound. pSWE can easily be performed on a conventional ultrasound machine as well, with no need for any special probe or machinery, but it does not have the ability to showcase images of tissue stiffness [52][53][54][55][56][57][58]. See Figure 2.…”
Section: Point Shear Wave Elastography (Pswe)mentioning
confidence: 99%
“…For example, ultrasound elastography techniques can be applied to characterize liver fibrosis and its stage in adult patients, such as vibration-controlled transient elastography, the most utilized and validated elastography method[ 86 ]. A meta-analysis study also showed that magnetic resonance elastography (MRE) and point-shear wave elastography (pSWE) can be applied for liver fibrosis diagnostic, and MRE is a more accurate imaging technique than pSWE[ 87 ]. The pooled sensitivities and specificities for MRE and pSWE were 0.94 (95% confidence level/CI: 0.89-0.97) and 0.95 (95%CI: 0.89-0.98), and 0.86 (95%CI: 0.80-0.90) and 0.88 (95%CI: 0.85-0.91), respectively.…”
Section: Current Diagnosis For Liver Fibrosismentioning
confidence: 99%